Analysis of shallow slope instability at an open-pit mine in Fuyang, China - Zhuzhe, Cheng (Frontiers in Earth Science, 2025)
This study examines the impact of rainfall-induced infiltration on the stability of shallow slopes at the open-pit mine in Fuyang, China. The objective was to elucidate the relationship between rainfall, soil moisture, and landslide initiation. Using COMSOL Multiphysics, the research simulated infiltration effects and identified the strongly weathered limestone at +250 m as a critical stability factor. Results showed increased pore water pressure and saturation levels with rainfall, particularly affecting the unsaturated zone. A high-risk landslide area was pinpointed between +250 m and +270 m. To mitigate risks, a reinforcement strategy with mini steel pipe piles was proposed. The study underscores the need for integrated data in predictive models to enhance landslide risk management in mining and other landslide-prone regions.